Driving U.S. Business Growth with AI-Driven Intelligent Automation: Building Decision-Making Infrastructure to Improve Productivity and Reduce Inefficiencies (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The swift development of smart automation, especially with the help of robotics and artificial intelligence (AI), is transforming the business operational and competitive strategies of businesses in the United States. With an increase in the cost of labor, worldwide competition and the growing complexities in supply chains, entities in all sectors are resorting to automation as a way of increasing their productivity, reducing inefficiencies and ensuring sustainable growth. The paper will discuss how automation through robotics will affect the development of businesses, particularly in terms of productivity, cost savings, and workforce. The study, based on the Industrial Robotics and Automation Dataset (2015 - 2023), in which the metrics include robotics adoption, productivity gains, cost reduction, job displacement, and training hours, gives an overall assessment of the role of automation in the contemporary business transformation. According to the findings, automation is always effective in enhancing efficiency and lowering costs of operation; however, the impact varies across industries. The most productive growth is found in manufacturing, but with high demands of reskilling the workforce. Adaptive training requirements lead to moderate efficiency increase in logistics and marginal productivity growth in healthcare where minimal disruption in the workforce is caused by human-centric nature of patient care. Temporal analysis demonstrates that the pace of automation adoption and productivity increases accelerated after 2020, which can be attributed to the impact of the COVID-19 pandemic, which pushed the digital transformation process and changed the priorities related to the operations. Other than economic results, the paper also outlines the two-dimensional problem of displacement of the workforce and the need to have training programs in order to create a fair adaptation. Finally, the study highlights the fact that intelligent automation is not merely an instrument of efficiency in operations, but also a long-term competitiveness force. These lessons can be of great value to policy makers, industry leaders, and researchers to balance between technological development and workforce sustainability in order to enhance inclusive business development in the U.S. economy.